Colorectal cancer mortality in women: trend analysis in Brazil and its regions and states - Barbara Aparecida Dobiesz; Rosana Rosseto de Oliveira; Makicilene Paranho de Souza; Raíssa Bocchi Pedroso; Kely Paviani Stevanato; Fernando Castilho Pelloso; Maria Dalva de Barros Carvalho; Sandra Marisa Pelloso (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to analyze colorectal cancer mortality trends in women in Brazil and its regions and states. Methods: ecological, time-series study with trend analysis of deaths caused by colorectal cancer in women in Brazil and its regions and states between 2008 and 2019. Polynomial regression was used to treat the data. Results: 48,225 deaths of women caused by colorectal cancer were examined. There was an increasing mortality trend in Brazilian women, with regional differences that resulted from socioeconomic, political, and cultural inequalities. The South Region stood out with the highest rate (7.32) in 2008, which increased to 8.65 in 2019, followed by the Southeast Region, whose rates were 6.72 and 9.05 in 2008 and 2019, respectively. Conclusions: colorectal cancer mortality increased, which indicates the need to expand public policies oriented toward screening and early diagnosis of colorectal cancer in women.